Analysis of the correlation between Hashimoto’s thyroiditis and food intolerance - Yan, Manli; Wu, Hai; Zhang, Kaiyuan; Gong, Ping; Wang, Yiting; Wei, Hua (Frontiers in Nutrition, 2024)
Objective This study aims to explore the correlation between patients with Hashimoto’s thyroiditis and food intolerance. Methods A total of 172 subjects who visited Guangdong Provincial Hospital of Traditional Chinese Medicine between January 2020 and March 2023 were selected and tested for 90 food-specific IgG antibodies. The study group composed 85 individuals diagnosed with Hashimoto’s thyroiditis, while the control group consisted of 87 healthy individuals. Data were analyzed to determine the correlation between Hashimoto’s thyroiditis and food intolerance. Results Among the 85 patients with Hashimoto’s thyroiditis, 97.65% exhibited food intolerance, with an average of 15.76 ± 10.61 types of food intolerances. The most common intolerances were to eggs (75.29%), bok choy (71.76%), and milk (65.88%), each exceeding a 60% intolerance rate. In the control group of 87 healthy individuals, the intolerance rate was 95.40%, with an average of 9.57 ± 8.90 types of food intolerances. The most prevalent intolerances in the control group were to bok choy (54.02%) and eggs (52.87%), each exceeding a 50% intolerance rate. Conclusion The findings suggest that patients with Hashimoto’s thyroiditis are more likely to develop food intolerance compared to the healthy population, which may indicate a correlation between Hashimoto’s thyroiditis and food intolerance. Different dietary patterns may affect the activity of the thyroid axis and may even be the cause of autoimmune thyroid disease. The technique of detecting food intolerance IgG antibodies has the potential to be an important reference for dietary interventions in patients with Hashimoto’s thyroiditis.